2017
DOI: 10.1002/2017gl073714
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface intensification of marine heatwaves off southeastern Australia: The role of stratification and local winds

Abstract: Marine heatwaves (MHWs) are becoming more common with record events occurring around the world and unprecedented biological impacts including mass mortality and habitat shifts. However, little is known about the statistical characteristics of MHWs due to the lack of long‐term in situ observations. Using two historical data sets spanning from 1953 (and 1992) to 2016, we use a seasonally varying climatology and temperature anomalies to identify and characterize MHW events down to 100 m depth in coastal waters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 49 publications
4
112
1
Order By: Relevance
“…For example, they have triggered widespread mortalities and abrupt redistribution of marine species (Garrabou et al, ; Wernberg et al, ), toxic algal blooms (Cavole et al, ), and mass coral bleaching (Hughes et al, ) in a matter of weeks or months, with economic losses in fisheries and aquaculture industry (Mills et al, ; Oliver et al, ). Superimposed on the underlying warming trend of the ocean, MHWs occur regionally from coastal to open ocean, can extend up to thousands of kilometers (Scannell et al, ), and may also propagate deeper to the water column (Schaeffer & Roughan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they have triggered widespread mortalities and abrupt redistribution of marine species (Garrabou et al, ; Wernberg et al, ), toxic algal blooms (Cavole et al, ), and mass coral bleaching (Hughes et al, ) in a matter of weeks or months, with economic losses in fisheries and aquaculture industry (Mills et al, ; Oliver et al, ). Superimposed on the underlying warming trend of the ocean, MHWs occur regionally from coastal to open ocean, can extend up to thousands of kilometers (Scannell et al, ), and may also propagate deeper to the water column (Schaeffer & Roughan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet it remains unknown how frequently and deep a MHW may penetrate in the open ocean or what are the characteristics of deep events relative to surface MHWs. The only systematic analysis to date is based on coastal in situ data in Australia for 1953–2016 and shows regular warming throughout the water column and a maximum MHW intensity just below the thermocline (Schaeffer & Roughan, ). In the case of the Mediterranean Sea, a quantitative assessment using a standarized framework is currently missing for both past surface and subsurface MHWs characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The ranges of uncertainty that sub-optimal data introduce into MHW results could be determined and users may now decide their acceptable level of uncertainty. It must be noted that having used only SST data for these investigations the results may not accurately represent the properties of sub-surface MHWs, which may last longer and be more intense than those at the surface (Schaeffer and Roughan, 2017;Darmaraki et al, 2019). The MHW results from time series with 10 years of data are not appreciably different from the MHWs detected with 30 years of data.…”
Section: Discussionmentioning
confidence: 83%
“…This sentiment reflects that of previous research, whereby Smale and Wernberg (2009) concluded that satellite SST data do not "adequately detect ecologically important small-scale variability or provide reliable information on temperature extremes" and Stobart et al (2016), who highlighted that SST was only reliable for broad temperature patterns. These, together with increasing frequency of extreme temperature events (e.g., marine heatwaves; Schaeffer and Roughan, 2017), makes long-term monitoring programs critical especially those that provide high resolution temperature over a range of spatial scales (including depth).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Therefore, long-term in situ monitoring is needed for water depths >16 m, as this is information that is not available from satellite data. It has been shown that extreme marine temperature events (e.g., marine heatwaves: Schaeffer and Roughan, 2017) can occur throughout the water column, and their intensity and duration may be either not detected or underestimated by satellite SST. Such events can have devastating consequences on marine biota (Smale and Wernberg, 2012;Wernberg et al, 2013).…”
Section: Satellite-derived Temperaturesmentioning
confidence: 99%